Etude De Quelques Caracteristiques Physicochimiques Et Biochimiques De Wavé-fortex Un Complement Alimentaire Naturel Du Gabon - Lepengue, Alexis Nicaise; Souza, Alain; Yala, Jean Fabrice; Lebamba, Judicaël; Mavoungou, Jacques; M’batchi, Bertrand (European Scientific Journal, ESJ, 2016)
Wavé-fortex is a dietary supplement designed to Gabon, to fight against the problems of malnutrition and undernourishment. It would also contain diuretic properties, purgative, antimicrobial, aphrodisiac, influenza, regulating blood pressure, reducing overweight and stimulating sperm production. This work was carried out to study the physicochemical and biochemical characteristics of this health food. The results revealed that Wavé-fortex was heavily dehydrated and contained 6.27% of crude ash and 11.32% of total gross fibers. The mineral level, Wavé-fortex contains 1.27% of calcium, 0.09% of iron, 0.37% of magnesium, 0.87% of potassium and 0.01% of zinc. Biochemical analyzes showed that this functional food contained 45.69% of carbohydrates, 26.01% of protein and 4.67% of fat. This gives it an energy value of 3.55 kcal / g of dry matter. Wavé-fortex is an acidic product (pH 4.02) with high levels of vitamin A (2.38%), vitamin C (1.93%) and phenolic compounds (11.83%). The different levels of these compounds are capable of validating the various nutritional properties attributed to this food powder.